FACTORS AFFECTING STOCK RETURN OF CONSUMER GOODS SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE FOR THE 2017-2019 PERIOD - Riska Rosdiana (Dinasti International Journal of Education Management And Social Science, 2022)
This study aims to analyze the effect of Debt to Equity Ratio, Current Ratio, Net Profit Margin and Earning Per Share on Stock Return. The population in this study were 64 companies in the Consumer Good sector. The sample used is 39 companies. The sampling method used purposive sampling technique. This research data is in the form of secondary data. The data analysis techn3ique was carried out by panel data regression with the method chosen by the fixed effect model. The results of this study indicate that: (1) Debt to Equity Ratio (DER) has a negative and signicant effect on stock returns of companies in the consumer goods sector; (2) Current Ratio (CR) has a negative and significant effect on stock returns of companies in the consumer goods sector; (3) Net Profit Margin (NPM) has no effect on stock returns of companies in the consumer goods sector; (4) Earning Per Share (EPS) has no effect on stock returns of companies in the consumer goods sector.